Sistem Agro Konservasi Smart Biosoildam untuk Peningkatan Daya Dukung Tanah Litosol - Nugroho Widiasmadi (Departement of Mathematics Education, 2023)
The Civil Engineering Study Program of Ngurah Rai University (UNR) implements the core curriculum by including Material Mechanics as part of the 2020 curriculum. One of the Learning Outcomes of the Material Mechanics Course (CMPK) is that students are expected to be able to determine the core magnitude (kern) of building structure elements. The fulfillment of CMPK is targeted to achieve a minimum of 90% of lecture participants are able to determine the core magnitude (kern) of building structure elements, but the class action Cycle I with the treatment of including detailed and systematic answer substance requests that describe the complete solution of the problem can only increase the CMPK from 60% to 84%. For the purpose of achieving a minimum of 90% CPMK compliance, a Class Action Cycle II d is carried out by treating Cycle I plus providing examples of relevant questions. The evaluation was carried out using the Alternative Assessment Method to assess cognitive, psychomotor (skill) and affective (attitude) aspects. The results of class actions with structured assignment treatment include detailed and systematic requests for answer substance that describe the complete solution of the problem plus the provision of examples of relevant questions can increase the fulfillment of the CMPK of Mechanical Materials for Students of the Civil Engineering Study Program, Ngurah Rai University reaching 92%. This result is expected to be a reference for other eyes in achieving the CMPK reduction target.